2006
DOI: 10.1270/jsbbs.56.119
|View full text |Cite
|
Sign up to set email alerts
|

Coat Protein Gene-Mediated Resistance to Soybean Mosaic Virus in Transgenic Soybean

Abstract: Somatic embryos of Glycine max (L.) Merrill cultivar 'Jack' were co-transformed with coat protein (CP) gene of attenuated isolates of soybean mosaic virus (SMV) and hygromycin phosphotransferase (hpt) gene by means of microprojectile bombardment. These transformed embryogenic tissues were selected in hygromycincontaining liquid medium. The hygromycin-resistant embryogenic tissues obtained through the selection were regenerated, and CP gene was detected in the 11 transgenic plants out of them. In order to asses… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 20 publications
0
18
0
Order By: Relevance
“…However, transformation can be applied to only a few soybean cultivars and the efficiency of transformation is low. Furthermore, long time (more than 1 year) is needed to obtain transformed soybeans (Furutani 2007;Tougou 2009). Several reports also showed that co-suppression by overexpression of a transgene were reset during the reproduction in several transgenic plants, including soybean plants (Aida and Shibata 1998;Furutani et al 2007;Mitsuhara et al 2002;Yamagishi et al 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…However, transformation can be applied to only a few soybean cultivars and the efficiency of transformation is low. Furthermore, long time (more than 1 year) is needed to obtain transformed soybeans (Furutani 2007;Tougou 2009). Several reports also showed that co-suppression by overexpression of a transgene were reset during the reproduction in several transgenic plants, including soybean plants (Aida and Shibata 1998;Furutani et al 2007;Mitsuhara et al 2002;Yamagishi et al 2006b).…”
Section: Discussionmentioning
confidence: 99%
“…The resistance did not need protein translated from the transgene [85][86][87], which led to the understanding that RNA is the factor that conferred resistance to the plants and that the enhanced resistance is acquired via a mechanism analogous to that involved in co-suppression. Using this strategy, soybean plants resistant to Soybean mosaic virus (SMV) [88][89][90], or Soybean dwarf virus [91,92] have been produced.…”
Section: Disease Resistance Acquired By Transgene-induced Rna Silencingmentioning
confidence: 99%
“…In another attempt by Furutani et al (2006), somatic embryos of Glycine max (L.) Merrill cultivar 'Jack' were co-transformed with coat protein (CP) gene of attenuated isolates of soybean mosaic virus (SMV) and hygromycin phosphotransferase (hpt) gene by means of microprojectile bombardment. These transformed embryogenic tissues were selected in hygromycin-containing liquid medium.…”
Section: Coat Protein-mediated Resistance (Cp-mr)mentioning
confidence: 99%